Características de la personalidad de un líder comunitario. - Alejandro Herrera, Marco Vinicio (My University, 2020)
The economic growth of the countries goes hand in hand with covering the basic needs of the communities. However, in developing countries such as Ecuador, the limitation of economic resources causes that there are needs in the neighborhoods that count with the presence of countless citizens who request to meet their requirements. Faced with these difficulties, community leaders appear as the people who influence their inhabitants in the search for resources through timely and intense management before the various authorities on duty. It is important that neighborhood boards have people who have the gift of leadership to meet their social goals and objectives. Situation that requires knowing the personality characteristics of the community leader to have a more precise idea when choosing the individual that represents the community. The objective of this essay is to investigate the personality characteristics of a community leader through the approach to urban organizations located south of the Machala canton. The modality of the essay was qualitative, the instrument applied was the interview and the technique was the bibliographic one for the compilation of articles related to community leadership.
El crecimiento económico de los países va de la mano con cubrir las necesidades básicas de las comunidades. Sin embargo, en países en proceso de desarrollo como Ecuador, la limitación de los recursos económicos provoca que haya necesidades en los barrios que cuentan con la presencia de un sinnúmero de ciudadanos que solicitan cubrir sus requerimientos. Ante estas dificultades aparecen los líderes comunitarios quienes se erigen como las personas que influyen en sus habitantes para la búsqueda de recursos a través de la gestión oportuna e intensa ante las diversas autoridades de turno. Siendo importante que las juntas barriales cuenten con personas que tengan el don de liderazgo para cumplir con sus objetivos y metas de índole social. Situación que requiere conocer las características de la personalidad del líder comunitario para tener una idea más precisa al momento de escoger al individuo que represente a la comunidad. Como objetivo el presente ensayo intenta indagar las características de la personalidad de un líder comunitario a través del acercamiento a las organizaciones urbanas ubicadas al sur del cantón Machala. La modalidad del ensayo fue cualitativa, el instrumento aplicado fue la entrevista y la técnica fue la bibliográfica para la recopilación de artículos relacionados al liderazgo comunitario.
Keywords: LIDER; COMUNIDAD; CARACTERISTICA; PERSONALIDAD